The mechanism of expression in the mural formations of the Iraqi ceramist, Sajida Al-Mashaikhi (Journal of the College of Basic Education, 2022)
The current study, titled (The Mechanism of Expression in the Wall Formations of Iraqi Potters, Sajida Al-Mashaykhi), is based on a methodology based on three chapters.The first chapter includes a methodology that included the research problem, its importance, and the temporal and formal limits of the research, with a definition of the most important terms that were mentioned in the title of the research, with a procedural definition for each one, in addition to the goal to be achieved from this study through a series of epistemological procedures.The second chapter was devoted to the theoretical framework, which included three topics:- The mechanism of artistic expressionSocial and psychological influences in artistic expression in ceramic formation.- The interrelationship between expression and composition elements in artistic ceramics.